PERAN STRATEGIS PAJAK MEWUJUDKAN KEADILAN SOSIAL - Wahyudi (JOURNAL OF LAW AND NATION, 2022)
In the current era of digitalization, the function of kinship and mutual cooperation in building the nation and state is no longer carried out physically, so taxes are the main manifestation of commitment to the nation and state. In the Pancasila Democracy system, our common goal as a nation and state has been determined in the fifth sile, namely Social Justice for the All Indonesian Nation. To realize social justice, of course, it is necessary to develop economic, political, social, cultural, security and so on. From the perspective of economic development, taxes place themselves in a strategic role because taxes are a source of state revenue that contribute or contribute at least 80% of the total APBN (State Revenue and Expenditure Budget) each year.